High-performance supercapacitor electrode based on activated carbon fiber felt/iron oxides. (December 2019) - Rodrigues, A.C.; da Silva, E. Leal; Oliveira, A.P.S.; Matsushima, J.T.; Cuña, A.; Marcuzzo, J.S.; Gonçalves, E.S.; Baldan, M.R.
Highlights: A novel type of activated carbon felts/iron deposited were investigated as electrode material for supercapacitor. The process of deposition of iron was very simple, cheap and safe, giving a complex γ-FeOOH. γ-FeOOH deposited increase the conductivity and directly affected the capacitance. Abstract: Supercapacitors have received great attention in science and technology, due to its important qualities as the high cycle life, high power density, and variety of applications. The main challenge for the development of better devices is the electrode material. Developing electrode materials with high specific electrical capacitance and low electrical resistance enables an increase of energy accumulated in the supercapacitor. In addition, it is expected that the electrode material presents a simple procedure for preparation with low production cost and be friendly to the environment. In this work, a cheap and simple electroless process was involved to deposit chemical species of iron on a no expensive textile activated carbon fiber felt with interesting properties for application as supercapacitor electrode. The resulting binary composite (Fe@ACF) supercapacitor electrode possesses a high specific capacitance of 237 F g −1 at a current density of 0.2 A g −1 and only 3% of loss of its initial specific capacitance after 3000 charge-discharge cycles. These results reveal that the activated carbon fiber felt/iron composites are promising materials for supercapacitor electrode applications.